The interrelationship between the release of renin and vasopressin as defined by orthostasis and propranolol. - R Davies; M L Forsling; J D Slater (The Journal of Clinical Investigation, 1977)
The concentration of both plasma renin and plasma arginine vasopressin rose in normal subjects after an 85 degrees head-up tilt. Plasma renin activity, which increased 70-80% above the supine value, was maximal at 15 or 30 min, whereas the six- to seven-fold increase of plasma arginine vasopressin concentration was observed between 30 and 45 min. Intravenous propranolol administered just before tilt was used to investigate the possibility that the delayed rise of arginine vasopressin was stimulated by renin. Although the response of plasma renin was completely abolished by propranolol, the response of vasopressin was unaffected. These findings suggest that the release of vasopressin that follows isosmolar hypovolemia achieved by orthostasis may occur independently of changes in the renin-angiotensin system in the presence of propranolol.